2016
DOI: 10.1103/physrevb.93.161302
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic wave absorption as a probe of dynamical geometrical response of fractional quantum Hall liquids

Abstract: We show that acoustic crystalline wave gives rise to an effect similar to that of a gravitational wave to an electron gas. Applying this idea to a two-dimensional electron gas in the fractional quantum Hall regime, this allows for experimental study of its intra-Landau level dynamical response in the long-wave length limit. To study such response we generalize Haldane's geometrical description of fractional quantum Hall states to situations where the external metric is time-dependent. We show that such time-de… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 45 publications
0
17
0
Order By: Relevance
“…Though alternative ways to test the internal geometry of gapped states have been put forward, e.g. by using acoustic wave absorption 27 , at this stage our knowledge comes almost exclusively from theory and numerics.…”
Section: Introductionmentioning
confidence: 99%
“…Though alternative ways to test the internal geometry of gapped states have been put forward, e.g. by using acoustic wave absorption 27 , at this stage our knowledge comes almost exclusively from theory and numerics.…”
Section: Introductionmentioning
confidence: 99%
“…The FQH graviton is hidden from conventional probes for collective modes such as inelastic light scattering [28][29][30][31] since these probes are limited to finite momenta. In contrast, recent works [36][37][38][39] have shown that the graviton can be directly excited in a dynamical quench experiment, where the band mass or dielectric tensor of the two-dimensional electron gas is suddenly made anisotropic or the magnetic field is abruptly tilted (see also a recent proposal using surface acoustic waves [40]). demonstrated that the theories of Refs.…”
Section: Introductionmentioning
confidence: 95%
“…To identify the collective modes more accurately, we perform a finer characterization of the dynamical response by choosing Ô in Eq. ( 24) to be one of the anisotropic pseudopotentials V σ m,s with a given chirality σ=± [36,40,82,83]. This allows us to probe systematically how the system responds to a particular type of metric deformation.…”
Section: Gmp Modementioning
confidence: 99%
“…79 It has been suggested that metric fluctuations produced by an acoustic wave might be used to excite quadrupolar modes of a gapped quantum state. 80 Geometric aspects of states in the lowest Landau level and their response to anisotropy have been emphasized in various investigations. [81][82][83] It is not entirely clear whether there should be unique definition of the shift parameter for a gapless state such as at ν = 1/2, and one must be careful about the proper definition of the Hall viscosity in this case.…”
Section: Issues Of Anisotropy and Geometrymentioning
confidence: 99%